An Improved DC Circuit Breaker Topology Capable of Efficient Current Breaking and Regeneration - Lumen, S.M.S. (Institute of Electrical and Electronics Engineers Inc., 2022)
The dc power system, due to its convenience of conversion, integration, and use, is getting immense attention in the field of power transmission and distribution. It is superior to the traditional ac systems in terms of efficiency, reliability, and control simplicity as well. A dc circuit breaker is one of the important elements of any dc power system. It is a sophisticated technology designed to break dc current only. The breaking of a dc current is always challenging compared with the breaking of an ac current, as dc current does not have natural zero crossing points like ac current has. Moreover, dc current breaking becomes more critical when the current is inductive as energy stored in the network inductance opposes instantaneous current breaking. Hence, this energy needs to be absorbed and dissipated as heat during the current breaking operation, which is exactly what is done in the traditional dc circuit breaker topologies. This article introduces a new topology for dc circuit breakers with a mechanism to reuse this stored energy instead of dissipating it. The mechanism is analogous to regenerative braking in electric drive systems and can enhance the overall system efficiency. The proposed scheme was analyzed through rigorous computer simulation and was experimentally validated. Â© 1986-2012 IEEE.